Association of KRAS gene mutations with depression in older metastatic colorectal cancer patients. (29th July 2016) - Zhou, Yi; Gu, Xiaohui; Wen, Feng; Chen, Jing; Wei, Wen; Zhang, Zhi-Hui; He, Yanting; Xie, Lan
ABSTRACT: Background: Cancer patients with depression or anxiety have poor survival, and the interaction between mental and physical problems in older patients may exacerbate this problem. K-ras oncogene ( KRAS ) mutation may play a role in the development of psychosocial distress and may be associated with poor survival of metastatic colorectal cancer (mCRC) patients. This study investigated the association between KRAS gene mutations and psychosocial morbidity to explore the possible cancer/psychosis relationship in older mCRC patients. Methods: In this study, 62 newly diagnosed mCRC patients were recruited and completed the Hospital Anxiety and Depression Scale (HADS). Demographic data were also collected, and clinicopathological data were retrieved from medical records. KRAS mutations were assessed via PCR analysis of tissue specimens from the patients. Results: The results showed that 28 of the 62 participants (45.2%) had positive screens for possible depression, and 45 of the 62 participants (72.6%) had positive screens for anxiety. The KRAS mutation rate was 40.3% (25/62), and 19 of the 25 patients with KRAS mutations (76.0%) had probable depression, whereas only 24.3% of the patients with wild-type KRAS were probably depressed ( p < 0.05). The KRAS mutation was associated with higher HADS depression scores, independent of gender and performance status ( p < 0.05), but not with higher HADS anxiety or total scores. Conclusions: KRAS mutations were associated with depression severity and higher rates of probable depression in older mCRC patients. Depression should be assessed and treated as early as possible in older mCRC patients with the KRAS mutation. Further studies are needed to verify our current findings using a larger sample size.